Estratégias de aprendizagem no ensino médio: implicações para a prática docente - Grehs, Bruna da Motta Signori (2020)
Knowing how to study and knowing how to learn is one of the most valuable skills students can have, especially High School students if considered that this is the school level with the biggest impact on the university and professional careers. Knowing the learning strategies that teenagers use or should use to learn better is essential when the goal is generating teaching goals. With this, the present study had as objective identifying and analyzing the learning strategies pointed out by teachers as effective and employed for the studies of High School students, by knowledge areas. It was an applied research, of descriptive and exploratory character, of qualitative quantitative data and field survey approach. The study included 90 teachers and 476 High School students from private and public schools located in the city of Foz do Iguaçu, Paraná. The instrument used was composed of a list with 20 strategies that should be highlighted by the participants, according to the relevance attributed to learning, by teachers and students and by knowledge area. The obtained data were analyzed by frequency and percentage. The results indicated that the learning strategies that teachers point out are most effective for their school subjects, demonstrating that most of the time teachers tend to select high utility strategies, while the students choose the low utility ones. It was also found that, in general, there is a divergence between the learning strategies that teachers point out and the ones that students say they use for their studies. It is concluded, that teachers have shown to be able to teach when and how to use specific learning strategies. Thus, this study is configured as a relevant contribution to the scarce literature on the subject in the Brazilian context, addressing High School and providing data for implication in the teaching practice, helping the teaching-learning process in the classroom. It should be noted that there is a presumption that students explicitly need stimulation of the cognitive skills through the systematic teaching of the learning strategies, in addition to the curriculum content.